Sex Hormone Binding Globulin Modifies Testosterone Action and Metabolism in Prostate Cancer Cells. (20th November 2016) - Li, Huika; Pham, Thy; McWhinney, Brett C.; Ungerer, Jacobus P.; Pretorius, Carel J.; Richard, Derek J.; Mortimer, Robin H.; d'Emden, Michael C.; Richard, Kerry
Abstract : Sex Hormone Binding Globulin (SHBG) is the major serum carrier of sex hormones. However, growing evidence suggests that SHBG is internalised and plays a role in regulating intracellular hormone action. This study was to determine whether SHBG plays a role in testosterone uptake, metabolism, and action in the androgen sensitive LNCaP prostate cancer cell line. Internalisation of SHBG and testosterone, the effects of SHBG on testosterone uptake, metabolism, regulation of androgen responsive genes, and cell growth were assessed. LNCaP cells internalised SHBG by a testosterone independent process. Testosterone was rapidly taken up and effluxed as testosterone-glucuronide; however this effect was reduced by the presence of SHBG. Addition of SHBG, rather than reducing testosterone bioavailability, further increased testosterone-induced expression of prostate specific antigen and enhanced testosterone-induced reduction of androgen receptor mRNA expression. Following 38 hours of testosterone treatment cell morphology changed and growth declined; however, cotreatment with SHBG abrogated these inhibitory effects. These findings clearly demonstrate that internalised SHBG plays an important regulatory and intracellular role in modifying testosterone action and this has important implications for the role of SHBG in health and disease.